2006
DOI: 10.1073/pnas.0600929103
|View full text |Cite
|
Sign up to set email alerts
|

Wild bees enhance honey bees’ pollination of hybrid sunflower

Abstract: Pollinators are required for producing 15-30% of the human food supply, and farmers rely on managed honey bees throughout the world to provide these services. Yet honey bees are not always the most efficient pollinators of all crops and are declining in various parts of the world. Crop pollination shortages are becoming increasingly common. We found that behavioral interactions between wild and honey bees increase the pollination efficiency of honey bees on hybrid sunflower up to 5-fold, effectively doubling h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
468
5
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 572 publications
(510 citation statements)
references
References 34 publications
21
468
5
16
Order By: Relevance
“…Moreover, the combination of A. mellifera and other bee species results in improvement of pollination in sunflower hybrids (DeGrandi-Hoffman and Watkins, 2000). Interactions between wild and honey bees increased five times the bee's efficiency pollination in sunflower hybrid (Greenleaf and Kremen, 2006). The same authors commented that indirect participations caused by interactions among bees species were five times most important than direct contributions of wild bees in sunflower pollination.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, the combination of A. mellifera and other bee species results in improvement of pollination in sunflower hybrids (DeGrandi-Hoffman and Watkins, 2000). Interactions between wild and honey bees increased five times the bee's efficiency pollination in sunflower hybrid (Greenleaf and Kremen, 2006). The same authors commented that indirect participations caused by interactions among bees species were five times most important than direct contributions of wild bees in sunflower pollination.…”
Section: Discussionmentioning
confidence: 85%
“…Greenleaf and Kremen (2006) observed interactions between wild bees and honey bees in which wild bees displaced honey bees from flowers. We also found that males of the red mason bee displace honey bees more often than vice versa, with male mason bees displacing intraspecific males and females as often as honey bees.…”
Section: Discussionmentioning
confidence: 99%
“…Although the extent to which 245 manage honey bees are competing with native bees is debatable, some studies have shown that 246 competition takes place with bumblebees for access to nectar (Thomson, 2004). For example, the 247 interaction between wild and honey bees contributes more than the direct contribution of the 248 commercial bees to the sunflower pollination (Greenleaf et al, 2006). These findings demonstrate 249 the economic importance of interspecific interactions for ecosystem services and suggest that the 250 protection of wild bee pollinators can help a lot the food production supply by compensating the 251 commercial bees' scarcity (Greenleaf et al, 2006).…”
Section: A Potential New Model To Quantify the Provision Of Pollinatimentioning
confidence: 99%
“…For example, the 247 interaction between wild and honey bees contributes more than the direct contribution of the 248 commercial bees to the sunflower pollination (Greenleaf et al, 2006). These findings demonstrate 249 the economic importance of interspecific interactions for ecosystem services and suggest that the 250 protection of wild bee pollinators can help a lot the food production supply by compensating the 251 commercial bees' scarcity (Greenleaf et al, 2006). This can promote variation in the pollination 252 service delivery that is difficult to take into account in the model.…”
Section: A Potential New Model To Quantify the Provision Of Pollinatimentioning
confidence: 99%